New insights into the spatial variability of microbial diversity and density in peatlands exposed to various electron acceptors with an emphasis on methanogenesis and CO2 fluxes - Shabbir, Sadaf; Qian, Chang; Faheem, Muhammad; Zhou, Fengwu; Yu, Zhi-Guo (Frontiers in Microbiology, 2024)
Peatlands are vital in the global carbon cycle, acting as significant sinks for carbon and releasing methane (CH4) and carbon dioxide (CO2) into the atmosphere. However, the complex interactions between environmental factors and the microbial communities responsible for these greenhouse gas emissions remain insufficiently understood. To address this knowledge gap, a pilot-scale mesocosm study was conducted to assess the impact of different terminal electron acceptors (TEAs), including sulfate (SO42−), humic acid (HA), and goethite, on CH4 and CO2 emissions and microbial community structures in peatlands. Our results revealed that the addition of TEAs significantly altered the CH4 and CO2 emissions. Specifically, the addition of SO42− nearly doubled CO2 production while substantially inhibiting CH4 emissions. The combined addition of SO42− and HA, as well as HA alone, followed a similar pattern, albeit with less pronounced effects on CH4. Goethite addition resulted in the highest inhibition of CH4 among all treatments but did not significantly increase CO2 production. Community composition and network analysis indicated that TEAs primarily determined the structure of microbial communities, with each treatment exhibiting distinct taxa networks. Proteobacteria, Acidobacteria, Chloroflexi, and Bacteroidetes were the most abundant phyla across all mesocosms. The presence of methanotrophs, including Methylomirabilales and Methylococcales, was linked to the inhibition of CH4 emissions in these mesocosms. This study provides novel insights into the spatial variability of microbial diversity and density in peatlands under various TEAs, emphasizing the role of methanogenesis and CO2 fluxes in carbon cycling. Our findings enhance the understanding of carbon cycling in microbe-rich environments exposed to TEAs and highlight the potential for future studies to investigate the long-term effects of TEAs on microbial communities, enzymes, and carbon storage.